2021
DOI: 10.1002/dc.24848
|View full text |Cite
|
Sign up to set email alerts
|

Atypical cells in fine needle aspiration biopsies of pancreas: Causes, work‐up, and recommendations for management

Abstract: Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is a sensitive and specific method for diagnosing cancer in solid pancreatic masses. However, some cases receive indeterminate atypical diagnoses, which creates management dilemmas. In the 2014 Papanicolaou Society of Cytopathology (PSC) standardized guidelines for pancreatobiliary cytology, specimens in the "Atypical" category show a spectrum of architectural and/or cellular changes beyond normal or reactive, but, quantitatively or qualitatively, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…Our study found the ROM of the "atypical" category ranged from 28 to 100%. Reporting under this category has been linked with significant interobserver variability; while reasons for an "atypical" interpretation include sample degeneration, limited cellularity, prominent reactive or dysplastic changes, gastrointestinal contamination, or inexperience of the pathologist [33]. Rapid on-site evaluation (ROSE) could reduce sampling artifacts during EUS-FNA [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found the ROM of the "atypical" category ranged from 28 to 100%. Reporting under this category has been linked with significant interobserver variability; while reasons for an "atypical" interpretation include sample degeneration, limited cellularity, prominent reactive or dysplastic changes, gastrointestinal contamination, or inexperience of the pathologist [33]. Rapid on-site evaluation (ROSE) could reduce sampling artifacts during EUS-FNA [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems to be of reduced value in pancreatic cystic lesions [35]. Reduction in "atypical" interpretations could be reached by applying ancillary techniques like immunohistochemistry or next-generation sequencing, asking help from experts, or performing a repeat FNA [33,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…There are situations where reactive acini in pancreatitis could be misinterpreted as acinar cell neoplasia on cytology specimens [ 12 , 21 ]. HooKim et al [ 5 ] demonstrated that the presence of syncytial clusters, prominent cherry red nucleoli and necrosis could be useful clues for the distinction between reactive pancreatic acini and ACC. ACC may show overlapping cytologic features with intraductal oncocytic papillary neoplasm; however, ACC is more mitotically active, and demonstrates a necrotic background [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic ultrasound–guided fine needle aspiration (EUS-FNA) is a well-established diagnostic method for solid pancreatic tumors, and thus an accurate diagnosis on aspiration cytology material is essential to guide the next steps for patient management [ 4 , 5 ]. While conventional smear (CS) cytology was the standard method for processing EUS-FNA cytology specimens, CS preparations often result in bloody smears, dry artifacts, and crushing artifacts, which could obscure the cytologic features and result in a suboptimal diagnosis [ 6 ].…”
mentioning
confidence: 99%